2017
DOI: 10.4103/0366-6999.220304
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Proton-pump Inhibitors on the Pharmacodynamic Effect and Clinical Outcomes in Patients Receiving Dual Antiplatelet Therapy after Percutaneous Coronary Intervention

Abstract: Background:Prior studies have reported controversial conclusions regarding the risk of adverse cardiovascular events in patients using proton-pump inhibitors (PPIs) combined with clopidogrel therapy, causing much uncertainty in clinical practice. We sought to evaluate the safety of PPIs use among high-risk cardiovascular patients who underwent percutaneous coronary intervention (PCI) in a long-term follow-up study.Methods:A total of 7868 consecutive patients who had undergone PCI and received dual antiplatelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…The results of the study and a systematic review clearly showed that clopidogrel-induced inhibition of platelet aggregation is weakened by the co-administration of PPIs, although some reports showed that rabeprazole, which is not mainly metabolized by CYP2C19, did not statistically significantly attenuate the anti-thrombotic effect of clopidogrel. [49][50][51][52] This consistent pharmacodynamic study result, however, was not confirmed in clinical studies. Firstly performed epidemiological study supported this concept and suggested that PPIs interfered with clopidogrel activation and elevated cardiovascular risk.…”
Section: Drug Interaction During Activation And/or Degradation Phase mentioning
confidence: 72%
“…The results of the study and a systematic review clearly showed that clopidogrel-induced inhibition of platelet aggregation is weakened by the co-administration of PPIs, although some reports showed that rabeprazole, which is not mainly metabolized by CYP2C19, did not statistically significantly attenuate the anti-thrombotic effect of clopidogrel. [49][50][51][52] This consistent pharmacodynamic study result, however, was not confirmed in clinical studies. Firstly performed epidemiological study supported this concept and suggested that PPIs interfered with clopidogrel activation and elevated cardiovascular risk.…”
Section: Drug Interaction During Activation And/or Degradation Phase mentioning
confidence: 72%
“…Other important predictors of MACE in our local population include diabetes, Malay ethnic group (compared to Chinese) and PPI use. Several meta‐analyses, registry and observational studies suggest no impact of PPI on clopidogrel MACE rates; however, a study on genetic cofactors, investigating the effect of omeprazole use on platelet reactivity, revealed that the only predictor of poor response was the presence of CYP2C19*2 mutation . It could be surmised that drug–gene interactions could be more significant when polymorphisms were more prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…was the presence of CYP2C19*2 mutation. [18][19][20][21][22] It could be surmised that drug-gene interactions could be more significant when polymorphisms were more prevalent. Based on the incidence rates of MACE in the PM vs NM population in our study, for a 95% confidence interval and 80% analysis, a mere 121 subjects are required and thus would likely be adequately powered.…”
Section: Ta B L Ementioning
confidence: 99%
“…Lower levels of the active metabolite of clopidogrel and higher residual platelet reactivity to ADP were described in clopidogrel-treated patients who concomitantly received PPIs. [59][60][61] This may be due to a drug interaction at the level of hepatic biotransformation of clopidogrel to its active metabolite by the cytochrome P450 enzyme system and was seen particularly in patients receiving omeprazole. 59,61 However, in the prospective and randomized Clopidogrel and the Optimization of Gastrointestinal Events Trial (COGENT), the authors observed no difference in the occurrence of adverse cardiovascular outcomes between clopidogrel-treated patients on omeprazole therapy and those receiving placebo.…”
Section: Discussionmentioning
confidence: 99%